Monopoles, vortices and their correlations in SU(3) gauge group - N. Karimimanesh; S. Deldar; Z. Asmaee (European Physical Journal C: Particles and Fields, 2023)
Abstract Topological defects such as monopoles, vortices and “chains” of the SU(3) gauge group are studied using its SU(2) subgroups. Two appropriate successive gauge transformations are applied to the subgroups to identify the chains of monopoles and vortices. Using the fact that the defects of the subgroups are not independent, the SU(3) defects and the Lagrangian are studied and compared with the Cho decomposition method obtained for monopoles. By comparing the results with the ones which are obtained directly for the SU(3) gauge group, the relations and the possible interactions between the defects of the subgroups are discussed.